- Pentingnya Penerapan Akuntansi Ponpes: Pesantren Tarbiyah Islamiyah Pariangan: - - Adella Fitri, Sri; Futri Nabilla, Suci; Ashifa Karim, Regina; Nasution, Riski; Ayunda, Tiara; Sari, Ermila (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
Some of the phenomena that occur are that there are still many Islamic boarding schools that do not apply accounting to the recording of their financial statements. Therefore, this study was conducted to find out how the application of accounting at the Tarbiyah Islamiyah Pariangan Islamic Boarding School, and see how the financial reporting is. This research was conducted using the research method used is a qualitative research method, the sampling technique is by documentation and interview techniques. The results of the research obtained are, financial statements in the form of accountability reports. Tarbiyah Isamiyah Islamic Boarding School in recording its financial statements still has not applied accounting in it. Keywords: Islamic Boarding School, Islamic Boarding School Accounting, Financial Managemen